Prospects for eliminating non-tariff distortions - Scaperlanda, Anthony Edward (Leiden, Sijthoff, 1973)
The present volume presents the results of the research undertaken by or in cooperation with the John F. Kennedy Institute.
Includes bibliographical references.
osc 11/07/2018
Loans
Keywords: Non-tariff trade barriers; Free trade; Protectionism